2017
DOI: 10.3892/ijo.2017.4126
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ERK and AKT pathways by hepatitis B virus X protein via the Notch1 pathway in hepatocellular carcinoma

Abstract: Hepatitis B virus (HBV) is the dominant risk factor for hepatocellular carcinoma (HCC). HBV X protein (HBx) plays crucial roles in HCC carcinogenesis. HBx interferes with several signaling pathways including the Notch1 pathway in HCC. In this study, we found that Notch1 was highly expressed in HCC, especially in large HCCs. Notch1 and HBx co-localized in HCC and their levels were positively correlated with each other. Notch1 expression was more elevated in HepG2.2.15 cells than that in HepG2 cells. HBx activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(38 reference statements)
0
15
0
Order By: Relevance
“… 88 HBx relieves the inhibition of ERK by activating Notch signaling, which promotes the growth of HCC. 89 HBcAg induces the upregulation of B7-H1 through the activation of the Akt, ERK, and P38 signaling pathways, which inhibits the clearance of HBV DNA and promotes the apoptosis of dendritic cells, 90 thereby benefiting HBV to evade immune surveillance.…”
Section: Hbv Involved In Activation Of Tumor-promoting Signaling Pathwaysmentioning
confidence: 99%
“… 88 HBx relieves the inhibition of ERK by activating Notch signaling, which promotes the growth of HCC. 89 HBcAg induces the upregulation of B7-H1 through the activation of the Akt, ERK, and P38 signaling pathways, which inhibits the clearance of HBV DNA and promotes the apoptosis of dendritic cells, 90 thereby benefiting HBV to evade immune surveillance.…”
Section: Hbv Involved In Activation Of Tumor-promoting Signaling Pathwaysmentioning
confidence: 99%
“…Interestingly, Zhou et al [ 20 ] reported that TRIP13 promotes the proliferation and invasion of epithelial ovarian cancer through Notch signaling pathway. Liao et al [ 21 ] found that hepatitis B virus X protein can activate the Notch pathway, thus promoting the development of liver cancer. In the study by Li et al [ 22 ] miR-1179 was found to inhibit the metastasis of breast cancer cells by inhibiting Notch signaling pathway and Hes1.…”
Section: Resultsmentioning
confidence: 99%
“…All these in vitro as well as in vivo data have indicated an inhibition effect of EGFL8 on Notch signaling pathway in HCC. Furthermore, we treated EGFL8 depleted Hep3B cells with DAPT, an inhibitor of Notch signaling pathway [ 21 , 29 ], and found this treatment obviously inhibit the expression of Notch signaling pathway and significantly suppressed the migration, invasion, and survival of Hep3B cells which had been remarkably enhanced by EGFL8 knockdown, suggesting the modulation of EGFL8 on liver cancer cell metastasis and apoptosis is, at least partially, depend on the inhibition of Notch signaling pathway. However, the specific molecular mechanism underlying the regulation of EGFL8 on Notch signaling pathway remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%